Automated Air Conditioner Controler and Monitoring Based on Internet of Things - Mas Aly Afandi; Silvi Nurandi; I Ketut Agung Enriko (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2021)
Air conditioner make electricity demand becomes higher over time. International Energy Agency (IEA) shows that electricity consumption for air conditioner will be the main trigger for the increase in world electricity demand in 2050. Higher electricity demand caused by inefficient usage of air conditioner due to human error factors. Human error that mostly happen is forget to turn off the air conditioner. This condition make air conditioner will be operate all day. This research is aim to reduce human error case that happened by making automated air conditioner controller and monitoring based on internet of things. This research use passive infrared sensor as an input to make sure air conditioner in the room is used or not and temperature sensor DHT 11 to make sure air conditioner operation. Internet of things technology is used to monitor the output from the system and control the device. Data test shows that the device works well. Air conditioner controller device works as the command and scenario that given. Error reading for temperature sensor is 0.29% and best configuration for infrared transmitter and passive infrared at radius 90°.